2010
DOI: 10.1021/es100514x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for Biological Nitrogen Removal Using Shortcut Nitrification-Denitrification Process in Sequencing Batch Reactor

Abstract: A kinetic model for shortcut nitrification-denitrification process with sequencing batch reactor (SBR) was developed. To test this model, the kinetic parameters of the model including maximum specific rates and half-maximum rate concentrations for shortcut nitrification and denitrification were estimated from the results obtained from a laboratory-scale SBR fed with a soybean curd processing wastewater (400-800 mg COD L(-1), 50-65 mg NH(4)(+)-N L(-1)) at 26 degrees C. In the nitrification step, two DO levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…2, showing the DO and pH evolution with nitrogen dynamics. The results indicate that evolution of DO and pH is consistent with the normal regulation during nitrification and denitrification (Gao et al 2010). Furthermore, incomplete nitrification to nitrite is independent of influent ammonia loadings and operation time.…”
Section: Characterization Of Treatment Performancesupporting
confidence: 71%
See 2 more Smart Citations
“…2, showing the DO and pH evolution with nitrogen dynamics. The results indicate that evolution of DO and pH is consistent with the normal regulation during nitrification and denitrification (Gao et al 2010). Furthermore, incomplete nitrification to nitrite is independent of influent ammonia loadings and operation time.…”
Section: Characterization Of Treatment Performancesupporting
confidence: 71%
“…Since short-cut nitrification occurred in this study, specific growth rate of AOB (l A ) (day -1 ) can be estimated by Eq. (4) (Gao et al 2010). In this equation, Y A (g VSS/ g COD) is the yield coefficient of AOB.…”
Section: Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…4 (Panel C). These results demonstrated that denitrification obeyed zero-order kinetics under both anoxic and aerobic/anoxic operating conditions which was corresponding to denitrification process in a biological nitrogen removal SBR (Gao et al, 2010). The denitrification rates of intermittent aeration and anoxic groups were 0.49 kg m À3 d À1 and 0.37 kg m À3 d À1 , respectively.…”
Section: Experiments II Of Nitrate Removal Performancementioning
confidence: 72%
“…Different models have been developed to describe NBND. 3,4 The ASM3 extended for two-step nitrification-denitrification 5 (referred in this work as 'extended ASM3') represents the most accurate model for the description of the ASP with NBND. This model describes the dynamics of the activated sludge with high accuracy and has been developed based on a strong physiological and biochemical basis, which make it an ideal tool for process understanding and 12 includes the quantification of energy storage in order to describe ready biodegradable substrate and oxygen uptake with higher accuracy.…”
Section: Introductionmentioning
confidence: 99%